Singapore - Bonetto, Cristian (Footscray, Victoria, Australia Lonely Planet Publications Pty Limited, 2015)
"Provides travel information about Singapore, including cultural attractions, dining, nightlife, shopping, and lodging."
At head of title: Lonely Planet.
Pull-out map, local secrets, expert recommendations.
Includes index.
Keywords: Singapore -- Guides; Singapore -- Guidebooks